Impact of Synaptic Neurotransmitter Concentration Time Course on the Kinetics and Pharmacological Modulation of Inhibitory Synaptic Currents - Barberis, Andrea; Petrini, Enrica Maria; Mozrzymas, Jerzy W. (Frontiers in Cellular Neuroscience, 2011)
The time course of synaptic currents is a crucial determinant of rapid signaling between neurons. Traditionally, the mechanisms underlying the shape of synaptic signals are classified as pre and postsynaptic. Over the last two decades, an extensive body of evidence indicated that synaptic signals are critically shaped by the neurotransmitter time course which encompasses several phenomena including pre- and postsynaptic ones. In particular, the agonist transient depends on neurotransmitter release mechanisms, diffusion within the synaptic cleft, spill-over to the extrasynaptic space, uptake and binding to postsynaptic receptors. Most estimates indicate that the neurotransmitter transient is very brief, lasting between one hundred up to several hundreds of microseconds, implying that postsynaptic activation is characterized by a high degree of non-equilibrium. Moreover, pharmacological studies provide evidence that the kinetics of agonist transient plays a crucial role in setting the susceptibility of synaptic currents to modulation by a variety of compounds of physiological or clinical relevance. More recently, the role of the neurotransmitter time course has been emphasized by studies carried out on brain slice models that revealed a striking, cell-dependent variability of synaptic agonist waveforms ranging from rapid pulses to slow volume transmission. In the present paper we review the advances on studies addressing the impact of synaptic neurotransmitter transient on kinetics and pharmacological modulation of synaptic currents at inhibitory synapses.